PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN LINGKUNGAN DESA HANUA PULANG PISAU KALIMANTAN TENGAH - Halim, Abdul; Rahayu, Helda; Anastasia S., Clara; Ika Susanti, Devita; Maharani N., Grace; Dio, Noperi; Priskila, Resty; Riko; Prima Sitepu, Rizal; Nurhani, Sarina; Bellamy D., Yorick; Yusnia; Dewi P.K., Wulan; Juanabel R., Zefanya (UNIVERSITAS SERAMBI MEKKAH, 2024)
Regular Thematic Community Service (KKN-T) Period I in 2024 was held in Hanua Village, Banama Tingang District, Pulang Pisau Regency, Central Kalimantan, with the main objective of improving community welfare through the application of science by students of Palangka Raya University. This KKN program carries the theme